2009
DOI: 10.1007/s00104-009-1790-0
|View full text |Cite
|
Sign up to set email alerts
|

Disorders in urinary bladder micturition after rectal operations

Abstract: Functional disorders of micturition after rectal resection in rectal cancer patients are commonly occurring complications which have received relatively little attention in the literature considering the clinical significance. Only few affected patients have received a urological treatment. Further studies are necessary, also experimental in nature, to understand the neuro-anatomy of the small pelvis in order to avoid intra-operative neurolesions as far as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Vesicourethral dysfunction occurs after LAR and APE in the early post-operative phase in 30 -70 % of patients if the autonomic nerves are not specifically preserved or cannot be correctly identified in an effort to preserve the nerves (1,76,77) Obstructive disorders after surgery attract more attention as they have to be treated acutely, although continence disorders are also common. A retrospective study (166) showed an increase of 19 % in imperative need to urinate post-operatively compared with 4% pre-operatively, from 9% to 26 % in pollakiuria and from 46.4% to 63% in nocturia, from www.intechopen.com…”
Section: Voiding Disorders After Larmentioning
confidence: 99%
“…Vesicourethral dysfunction occurs after LAR and APE in the early post-operative phase in 30 -70 % of patients if the autonomic nerves are not specifically preserved or cannot be correctly identified in an effort to preserve the nerves (1,76,77) Obstructive disorders after surgery attract more attention as they have to be treated acutely, although continence disorders are also common. A retrospective study (166) showed an increase of 19 % in imperative need to urinate post-operatively compared with 4% pre-operatively, from 9% to 26 % in pollakiuria and from 46.4% to 63% in nocturia, from www.intechopen.com…”
Section: Voiding Disorders After Larmentioning
confidence: 99%